Quality Approaches for the New Millennium - Cates, Christopher; Cates, Christopher; Demery, Angela; Hunzeker, Ryan (APQC American Productivity & Quality Center, 2000)
See how best-practice organizations use various quality approaches to achieve heightened levels of improvement, sustained competitive advantage, and long-term business excellence in Quality Approaches for the New Millennium.